If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2x-4=87
We simplify the equation to the form, which is simple to understand
2x-4=87
We move all terms containing x to the left and all other terms to the right.
+2x=+87+4
We simplify left and right side of the equation.
+2x=+91
We divide both sides of the equation by 2 to get x.
x=45.5
| g(p+4)=3x^2+5x+2 | | g(x)=3x^2+5x+2 | | 25x+13-19x-28=-18 | | (3x-4)=(2x+7) | | (x-2)(5x-9)=0 | | x+7x+3=180 | | 3-2x/4-5-3x/10=3/1-x/5 | | 3(x-4)+6x=3(2-x)*6 | | -6-3(-4)= | | -3+(-12)-5= | | -8-4x+11x+4=-53 | | 21+24=3(7+x) | | Ln^3x=4lnx | | 7x+6=4x-2 | | 3a+27=3-a | | 3c-5=1-c | | 1-2[5(3x-1)-5(1+2x)]=3(7-3x)-x | | 6x-8=4x-6 | | 2(x-3)+4=16 | | 3x+2x+35=180 | | 18X+Y=130 | | n+1.5n=24 | | 9x^2+12x-6d=0 | | 8=-x^2-12x | | X-3x+5=-7 | | 80g^2=45 | | 5(2m-9)=3(9-2n) | | 2(x+yi)=6-3i | | 4x(2x-7)=16 | | 5=(0+5)(0-3i) | | lnx=2*ln(3)-lnx | | 4y-(9-2y)+3(y-5)=4(y-1) |